Responses of senior citizens to disasters: a study with special reference to the tsunami and ethnic conflict (a case study of disaster affected areas in eastern sri lanka) - Ayoob, S.M. (University of Jaffna, 2012)
The main purpose of the study is to understand how senior citizens cope and withstand impacts of disaster and how they adapt to new ways of life resulting from disasters. In this study various methods were used for data collection from primary as well as secondary sources. Secondary data was collected from Divisional Secretariat, NGOs records, official records, previously conducted studies, books, publications, journal articles, reports, census data, internet and other relevant documents. Primary data were collected through a questionnaire survey, key informant interviews, Focus Group Discussions (FGDs) and case studies. The study found that prior to the disaster the senior citizens were leading a life of guide, adviser, mediator and decision maker in the family and community. In the social sphere they took part in social activities and also played a leadership role in religious activities. As far as economic activities were concerned senior citizens played a less active role. They mostly led a dependent and sedentary life. But, the disaster (Tsunami and ethnic conflict) had compelled more senior citizens to depend on themselves or forced to depend on them. They engaged themselves in economically productive life by involving in self employment etc to face the disaster and its losses.
Keywords: Disaster; Senior citizens; Leadership